Application of the Jigsaw Cooperative Learning Model to Improve the Mathematical Problem Solving Ability of Class VIII-3 Students of SMP Negeri 5 Pematang Siantar Academic Year 2022/2023 - Agnes Lucyana Purba; Mangaratua Marianus Simanjorang (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims (1) to find out how the efforts are being made to improve the mathematical problem solving abilities of class VIII-3 students of SMP Negeri 5 Pematang Siantar through the jigsaw type cooperative learning model, (2) to find out how to increase the mathematical problem solving abilities of students in class VIII- 3 SMP Negeri 5 Pematang Siantar after the implementation of the jigsaw cooperative learning model. The subjects in this study were 30 students in class VIII-3 at SMP Negeri 5 Pematang Siantar. The object of this research is the application of the jigsaw cooperative model to improve the mathematical problem solving skills of class VIII-3 students of SMP Negeri 5 Pematang Siantar for the 2022/2023 academic year. This type of research is class action research (classroom action research). This research consists of two cycles. Before giving action, an initial ability test is first given to determine students' initial abilities. From the results obtained it can be concluded that the class has met the indicators of research success. The results of this study indicate that the jigsaw type cooperative learning model can improve the mathematical problem solving skills of students in class VIII-3 SMP Negeri 5 Pematang Siantar in the 2022/2023 academic year.